The distribution of income in Central America - Thomas Gindling; Juan Diego Trejos S. (Institute for the Study of Labor (IZA), 2013)
We document changes in income and earnings inequality in the five Central American countries from the early 1990s to 2009. In the 1990s Costa Rica had the most equal distribution of income in Central America, and one of the most equal distributions of income in Latin America. At the other extreme, Guatemala, Honduras and Nicaragua were among the most unequal countries in Latin America. Inequality in El Salvador was between these extremes. Then, in the first decade of the 21st century inequality in El Salvador and Nicaragua decreased while inequality in Costa Rica, Guatemala and Honduras increased. By 2009 levels of inequality in El Salvador and Nicaragua were similar to those in Costa Rica. In this paper, we examine why income and earning inequality differs between the five Central American countries, and why inequality decreased in El Salvador and Nicaragua but increased in Costa Rica, Guatemala and Honduras.
Keywords: O15; J31; O54; 330; income inequality; Central America; labour income